Salvia united: The greatest good for the greatest number. Issue 1 (1st February 2017) - Drew, Bryan T.; González-Gallegos, Jesús Guadalupe; Xiang, Chun-Lei; Kriebel, Ricardo; Drummond, Chloe P.; Walked, Jay B.; Sytsma, Kenneth J.
Abstract: Previous molecular phylogenetic research, based on chloroplast and nuclear ribosomal DNA data, has demonstrated that the large genus Salvia (Lamiaceae) is paraphyletic as traditionally circumscribed. However, neither relationships within Salvia s.l. nor within subtribe Salviinae have been evaluated using low‐copy nuclear gene regions. Here, we use two low‐copy nuclear gene regions ( PPR‐AT3G09060, GBSSI ) to further assess relationships of Salvia and related genera within Salviinae. Our results largely confirm results from previous studies based on chloroplast and nuclear ribosomal DNA. Based upon the phylogenetic results presented here, previous phylogenetic studies, and taxonomic, morphological, and practical considerations, we conclude that the botanical community would be best served by maintaining a broadly defined Salvia, including the five small embedded genera Dorystaechas, Meriandra, Perovskia, Rosmarinus, and Zhumeria as Salvia species. We subsequently present an updated circumscription of Salvia.